Identification of Impulse Buying Behaviour among Shopee Users in Sumatra Island - Irfan Alfandi; Rina Suthia Hayu (Jurnal Manajemen, 2025)
This study aims to analyse the effect of marketing strategies such as flash sale, cashback, pay later, and free shipping on Impulse Buying behaviour among student Shopee users on the island of Sumatra. Using a quantitative approach, data will be collected through questionnaires distributed to 140 respondents. This research focuses on the age range of 18 to 25 years. The results of this study are expected to enrich the literature on consumer behaviour in the e-commerce sector. The findings are also expected to help companies or organisations understand what factors can drive Impulse Buying and optimise their marketing strategies to be more attractive to consumers on the island of Sumatra. The results of this study indicate a significant effect on the Flashsale and Cashback Variables on Impulse Buying. However, the Paylater and Freeshipping Variables do not affect Impulse Buying.